2020
DOI: 10.3390/diagnostics10080567
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coagulation Parameters in Women Affected by Endometriosis: Validation Study and Systematic Review of the Literature

Abstract: The presence of endometriosis determines an inflammatory response locally. The objective of this validation study and systematic review was to assess systemic levels of coagulation and inflammatory parameters in women with or without the disease. We conducted a retrospective analysis of a database prospectively collected from January 2017 to February 2020 including n = 572 women who underwent laparoscopic surgery for endometriosis (cases, n = 324) or other benign gynecologic diseases (controls, n = 248). Infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…The close association of coagulation and inflammatory conditions has been known for a long time 8 . Current studies have showed that women with EMS appeared to be in a state of hypercoagulability and this coagulation dysfunction potentially attributed to the inflammatory nature of the ectopic lesions 9 11 . In recent years, the massive data of gene expression profile generated from high-throughput sequencing technology make it possible for us to explore the intrinsic mechanism of diseases at the molecular level 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The close association of coagulation and inflammatory conditions has been known for a long time 8 . Current studies have showed that women with EMS appeared to be in a state of hypercoagulability and this coagulation dysfunction potentially attributed to the inflammatory nature of the ectopic lesions 9 11 . In recent years, the massive data of gene expression profile generated from high-throughput sequencing technology make it possible for us to explore the intrinsic mechanism of diseases at the molecular level 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] The endometriosis tumor microenvironment is characterized by chronic inflammation and hypoxic conditions, and previous studies have shown that endometriosis patients are in a hypercoagulable state like OCCC. [ 9 , 12 ] Otherwise, angiogenesis, immune escape and metastasis facilitate tumor development, and all these processes involve activation of the coagulation system. Coagulation factors can participate in tumor progression through coagulation-dependent pathways (including fibrin formation, platelet recruitment, immunomodulatory responses, and tissue factor particle secretion) and non-dependent pathways (intracellular signaling).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature discloses several studies reporting an association between endometriosis and a procoagulant state. High tissue factor expression, 104 increased procoagulant microparticle levels, 39 and modest systemic changes of coagulation parameters 105 have been reported, but these variables did not translate into increased VTE rates. To date, no studies have shown that endometriosis is associated with an increased risk of VTE except during pregnancy.…”
Section: Endometriosis and Cardiovascular Diseasementioning
confidence: 92%